Penggunaan ragi roti (Saccharomyces cereviciae) secara in situ untuk meningkatkan respon kebal non-spesifik ikan nila (Oreochromis niloticus) - Rawung, Meilina E; Manoppo, Henky (e-Journal BUDIDAYA PERAIRAN, 2014)
The objetive of research was to examine the effect of yeast cell Saccharomyces cereviciae on non-specific immune response of nile tilapia, Oreochromis niloticus. Juveniles weighing 31.83 g in average were cultured in five concrete tanks with a density of 30 fish per tank. The fish were fed pellet supplemented with yeast cell at five different doses (0, 10, 20, 30, 40 g/kg pellet) for three consecutive weeks as much as 4%/bb/day, twice daily. At the end of feeding, three fish from each tank were sampled to measure the immune parameters namely total leucocyte count and phagocytosis activity of phagocyte cells. Research results showed that after three weeks of feeding, total leucocyte and phagocytosis activity of fish fed pellet supplemented with yeast cells were significantly different as compared to those of control fish.Â  The highest total leucocyte and phagocytosis activity were achieved in fish fed pellet supplemented with 10 g of yeast cells/kg pellet.Â  It was concluded that the use of yeast cells for three weeks could enhance the nonspecific immune response of nile tilapia. Keywords: Saccharomyces cerreviciae, nonspecific immune response, total leucocyte count, phagocytosis activity, nile tilapia, Oreochromis niloticus